THE LOCAL CREATIVE ADS ON SRITANJUNG FM TO INCREASE FINANCIAL REVENUE DURING COVID-19 PANDEMIC - Zainal Abidin Achmad; Juwito Juwito; Muhammad Saud (Bricolage : Jurnal Magister Ilmu Komunikasi, 2020)
The COVID-19 pandemic condition requires private radio managers’ creativity, one of which is the Sritanjung FM in the Banyuwangi Regency. Uniquely, as a cultural radio, Sritanjung FM advertising revenue increased precisely during the COVID-19 pandemic. This research uses a virtual ethnographic method that collects data offline and online. Researchers conducted direct observations of Sritanjung FM in Rogojampi District, Banyuwangi Regency, and conducted a virtual search through audio streaming, Facebook, and WhatsApp. In this study, informants amounted to four people, two from radio staff, one cultural expert, and one loyal listener. The results showed that the number of local advertisers and the frequency of local advertisements had increased three times. The internal causes include the creativity of Sritanjung FM in creating cultural programs and religious programs, creativity in the designing messages for ads spots, and uniqueness of using local language that match the COVID-19 theme. Local culture advertising creativity can be felt as the main taste of content that has relevance to postmodernism studies. External causes include the need for a business breakthrough to maintain income, the socio-cultural context of Osing ethnicity for the Banyuwangi people. Combined interest between local advertisers, strong Osing culture identity, and advertisers' creativity make Sritanjung FM experience a surge in revenue from local advertisers during the COVID-19 pandemic.